A practice-grounded approach to 'engagement' and 'motivation' in networked learning - Dohn, Nina Bonderup (Proceedings of the International Conference on Networked Learning, 2014)
The aim of this paper is to clarify and challenge contemporary views of motivation and engagement as they appear within the networked learning literature and to suggest an approach which takes into account the insights of the prevailing individualist-cognitivist and socio-cultural views whilst accommodating better to seemingly well-known everyday cases. This approach supplies a more adequate instrument for analysing networked learning activities in that it highlights the complex interplay of the socially negotiated and the self-directedly chosen in the determination of a person's motivation and engagement. I identify two different metaphors of context - as 'container' and as 'rope' - drawn on by the individualist approach and the socio-culturalist approach, respectively, and argue that we need both metaphors to analyse motivation and engagement in networked learning activities. Drawing on the concept of primary contexts, I argue for a practice-grounded intermediary position which makes it possible to investigate empirically how different practices take on the significance of 'rope' or 'container' to a person at different points in his/her life. The phenomena of motivation and engagement are characterised as a complex set of states and processes, anchored in the individual, but partly co-constituted through positioning and negotiation in social space. I illustrate how complexly these phenomena relate to practices regarded as 'ropes'/'containers'. Distinguishing between a level of discrimination between practices and a level of concrete actions, I pinpoint important questions to investigate when analysing networked learning. By way of concluding, I briefly consider some implications for the design of networked learning.